PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN DAN DESENTRALISASI TERHADAP KINERJA MANAJERIAL DENGAN KONSEP LOCUS OF CONTROL (STUDY KASUS PADA RESEARCH AND DEVELOPMENT CENTER PT. TELEKOMUNIKASI INDONESIA, Tbk. BANDUNG) - Aditya Achmad Fathony; Husaeri Priatna; Ajeng Ferdikasari (AKURAT | Jurnal Ilmiah Akuntansi FE UNIBBA, 2018)
This research is conducted with a purpose: 1) To examine and analysis influence analysis of budgeting participation and decentralization toward managerial performance with locus of control concept on RDC PT. Telkom. 2) To examine and analysis dominant variable influence (budgeting participation or decentralization) toward managerial performance with locus of control concept on RDC PT. Telkom. Methods this study used a survey method, the type of data use qualitative data and quantitative data, the data source use primary data and secondary data. The population in this study was manager on RDC PT. Telkom. This research used 31 respondents with total sampling technique. Data collection methods were used: questionnaires, observation, and documentation. Data analysis technique used validity test, reliability test, the classical assumption test, multiple linear regression analysis, t test, F test, and coefficient of the determination